2018
DOI: 10.47203/ijch.2018.v30i01.008
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasitic Infestation in School Going Children of Rishikesh, Uttarakhand, India

Abstract: Background: Intestinal parasitism(IP) remains a common problem in school going children. Aims & Objectives: To study the prevalence IP infestation in school going children and to study the relation with type of water supply and sanitation. Material and Methods: A cross sectional study was carried out and a total of 461 stool samples were collected from children under ten years of age from various schools of Rishikesh. The normal saline and iodine mounts of fresh and saturated salt solution concentrated sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…54 In a systematic review published in 2016, the prevalence of AL, Ancylostoma duodenale and TT in 18 selected studies in India was in range between 0.4 and 71.87%, 0.14 and 42%, and 0.3 and 29.57%, respectively. 55 In our study, the prevalence of AL ranged from 0.8 18 to 91% 11 with a pooled prevalence of 25%. For TT, the prevalence ranged from 0.3 12 to 72% 11 with a pooled prevalence of 13%.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…54 In a systematic review published in 2016, the prevalence of AL, Ancylostoma duodenale and TT in 18 selected studies in India was in range between 0.4 and 71.87%, 0.14 and 42%, and 0.3 and 29.57%, respectively. 55 In our study, the prevalence of AL ranged from 0.8 18 to 91% 11 with a pooled prevalence of 25%. For TT, the prevalence ranged from 0.3 12 to 72% 11 with a pooled prevalence of 13%.…”
Section: Discussionmentioning
confidence: 52%
“…Though previous studies reported association of multiple risk factors with STH and other parasitic infections, data specific to our inclusion criteria is shown here. The more commonly studied risk factors included gender (10 articles), 10,13,[15][16][17][18][19][20][21][22] place of defecation whether in open or sanitary latrines (7 articles), 10,13,[15][16][17]23,24 hand washing after defecation with water only or soap and water (6 articles), 10,13,[15][16][17]23 socioeconomic status (SES) upper and middle versus lower (4 articles), 10,13,19,24 mother's education (4 articles), 10,13,16,19 barefoot walking (4 articles), 13,17,19,24 recent deworming(4 articles), 10,13,17,19 hygiene of finger nails (3 articles), 13,19,24 flooring earthen or cemented (3 articles), 10,13,15 religion (3 articles), …”
Section: Risk Factors Analysismentioning
confidence: 99%
“…Billions of people are affected globally, majority being school going children. Around 600 million school-age children live in areas where these parasites are endemic (Bansal et al, 2018) . Worm infestations have a close relationship with the socio-demographic and ecological factors like poverty, illiteracy, poor personal and environmental hygiene.…”
mentioning
confidence: 99%